(untitled) (TAMADDUN NURI JURNALI, 2025)
This article explores the linguistic development of the concept of «stepfather» in the English lexical system. The paper traces the historical evolution of the term «stepfather», analyzing its semantic shifts and role in family discourse. Through a combination of etymological analysis, corpus studies, and historical linguistic research, this paper outlines how the concept of «stepfather» emerged, transformed, and continues to evolve in contemporary English. The study highlights the cultural implications of the term, illustrating how it reflects social changes in family structures, especially in relation to remarriage and blended families.